Enhancing Understanding of Pancasila Values Through the Use of the Snake and Ladder Game as a Learning Media for Grade 1 Students at MI Nurul Hidayah Urangagung - Isma, Khilyatul; Syafi’, Moh. Agus Syairofi (Mentari : Journal of Islamic Primary School, 2025)
This article discusses the implementation of the educational snake and ladder game as a strategy to enhance students' understanding of Pancasila values in Pancasila Education for first-grade students at MI Nurul Hidayah Sidoarjo. The snake and ladder game is considered effective in conveying abstract concepts to early-age students as it fosters an active, enjoyable, and interactive learning atmosphere. This study employs a Classroom Action Research (CAR) method consisting of two cycles, with each cycle including the stages of planning, implementation, observation, and reflection. Data collection techniques used include tests, observation, and documentation. The results indicate a significant improvement in students' understanding, with the average score increasing from 63.08 in cycle I to 78.08 in cycle II, along with an increase in learning mastery from 30.7% to 92.3%. The novelty of this research lies in the integration of Pancasila values into a thematic game format accompanied by reflective activities. This study recommends the use of educational game media as an innovative approach in teaching Pancasila Education at the elementary school level.